Induction of Redox-Active Gene Expression by CoCl2 Ameliorates Oxidative Stress-Mediated Injury of Murine Auditory Cells - Jhang Ho Pak; Junyeong Yi; Sujin Ryu; In Ki Kim; Jung-Woong Kim; Haeri Baek; Jong Woo Chung (MDPI AG, 2019)
Free radicals formed in the inner ear in response to high-intensity noise, are regarded as detrimental factors for noise-induced hearing loss (NIHL). We reported previously that intraperitoneal injection of cobalt chloride attenuated the loss of sensory hair cells and NIHL in mice. The present study was designed to understand the preconditioning effect of CoCl2 on oxidative stress-mediated cytotoxicity. Treatment of auditory cells with CoCl2 promoted cell proliferation, with increases in the expressions of two redox-active transcription factors (hypoxia-inducible factor 1α, HIF-1α, nuclear factor erythroid 2-related factor 2; Nrf-2) and an antioxidant enzyme (peroxiredoxin 6, Prdx6). Hydrogen peroxide treatment resulted in the induction of cell death and reduction of these protein expressions, reversed by pretreatment with CoCl2. Knockdown of HIF-1α or Nrf-2 attenuated the preconditioning effect of CoCl2. Luciferase reporter analysis with a Prdx6 promoter revealed transactivation of Prdx6 expression by HIF-1α and Nrf-2. The intense immunoreactivities of HIF-1α, Nrf-2, and Prdx6 in the organ of Corti (OC), spiral ganglion cells (SGC), and stria vascularis (SV) of the cochlea in CoCl2-injected mice suggested CoCl2-induced activation of HIF-1α, Nrf-2, and Prdx6 in vivo. Therefore, we revealed that the protective effect of CoCl2 is achieved through distinctive signaling mechanisms involving HIF-1α, Nrf-2, and Prdx6.